The Role Of The Ditpamobvit Of Polda Bengkulu In Safeguarding Certain Vital Objects In Bengkulu Regional Police Jurisdiction - Adiromdani Adiromdani; Antory Royan Adyan; Herlambang Herlambang (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
This study aimed to investigate: (1) the role of the Directorate Unit of Vital Object Safeguarding (Ditpamobvit) of Polda Bengkulu in safeguarding certain vital objects in Polda Bengkulu jurisdiction, (2) the inhibiting factors for the implementation of safeguarding certain vital objects carried out by the Ditpamobvit of Polda Bengkulu. In this thesis research method, the type of research used is descriptive. This study is included as an empirical legal research and it obtained that: (1) the role of the Ditpamobvit of Polda Bengkulu in safeguarding certain vital objects in Polda Bengkulu jurisdiction is carried out with security activities prioritizing pre-emptive and preventive principles but if needed in dangerous situations and conditions, law enforcement treatments (repressive) are allowed, (2) the inhibiting factors for the implementation of safeguarding certain vital objects carried out by the Ditpamobvit of Polda Bengkulu include the lack of security coordination between the Ditpamobvit unit of Polda Bengkulu and the security management of the vital objects, the lack of security unit officers compared to the level of vulnerability of the objects so that there is the potential for security threats/ disturbances to arise, and the lack of security infrastructure such as: number of guard posts, surveillance cameras (CCTV), patrol car units, area lighting, communication tools, and detection tools (metal detector/ search mirror/ manual detection tools).